1998
DOI: 10.1063/1.367955
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of oriented thin films of PbZrO3 on Si produced by pulsed laser ablation

Abstract: Growth, microstructure, and ferroelectric properties of Pb ( Zr 0.4 Ti 0.6 ) O 3 ∕ Pb Zr O 3 superlattices prepared on Sr Ti O 3 (100) substrates by pulsed laser deposition Field-induced dielectric properties of laser ablated antiferroelectric ( Pb 0.99 Nb 0.02 )(Zr 0.57 Sn 0.38 Ti 0.05 ) 0.98 O 3 thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…PbZrO3, (Pb0.95Ba0.05)ZrO3 [PBZ (5) [18,19]. Barium acetate (99.5%, Sinopharm Chemical Reagent Co., Ltd., China), strontium acetate (99.9%, Sinopharm Chemical Reagent Co., Ltd., China), lead acetate trihydrate (99.5%, Sinopharm Chemical Reagent Co., Ltd., China) and zirconium isopropoxide (70% in propanol, Aldrich) were used as raw materials.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…PbZrO3, (Pb0.95Ba0.05)ZrO3 [PBZ (5) [18,19]. Barium acetate (99.5%, Sinopharm Chemical Reagent Co., Ltd., China), strontium acetate (99.9%, Sinopharm Chemical Reagent Co., Ltd., China), lead acetate trihydrate (99.5%, Sinopharm Chemical Reagent Co., Ltd., China) and zirconium isopropoxide (70% in propanol, Aldrich) were used as raw materials.…”
Section: Synthesismentioning
confidence: 99%
“…Hence, AFE materials have potential applications in micro-actuators, IR-detectors, digital memories, high energy storage capacitors and cooling devices [1][2][3][4]. Pure PbZrO 3 (PZ) with a Curie point of 230 • C is the most stable AFE material at room temperature [5]. PZ-based materials in bulk and film forms are also the most extensively investigated AFE materials at present.…”
Section: Introductionmentioning
confidence: 99%
“…Such PZ thin films, epitaxially grown on MgO substrates, achieves high dielectric constants which are nearly 2.4 times larger than that of bulk PZ [15]. Chattopadhyay et al [18] investigated PZ thin films on Si(100) substrates. They found an AFE [19].…”
mentioning
confidence: 98%
“…Ayyub et al [7] have shown that a typically antiferroelectric material PbZrO 3 or BiNbO 4 displays ferroelectric behavior below a critical film thickness characteristic of the system. Namely, 100nm PbZrO 3 /Si film has ferroelectric hysteresis loop, whereas 900 nm film posses the antiferroelectric one.…”
Section: Introductionmentioning
confidence: 99%
“…Chattopadhyay et al [3] demonstrated that thin PbZrO 3 films on Si substrate possess switchable polarization. Hung et al [4] have found that multilayer of PbZrO 3 /BaZrO 3 has ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%